Хемосорбція гексаметилдисилазану на поверхні пірогенного кремнезему, модифікованого оксидами титану та ванадію - Dyachenko, A. G.; Borisenko, N. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2003)
IR-spectroscopy, thermogravimetry, and mass spectrometry were used to investigate the effect of chemical modification of fumed silica surface with titanium and vanadium oxides on the chemisorption of hexamethyldisilazane. Titanium- and vanadium-containing silicas were synthesized by CVD-method by treatment with TiCl4 and VOCl3. The constants of rate and activation energy of hexamethyldisilazane reaction with initial silica and that modified with titanium and vanadium oxides have been determined. The thermal destruction of grafted -Si(CH3)3 groups was studied. It was found that the oxides of vanadium and titanium increase thermal stability of grafted groups in an oxidizing atmosphere and considerably decrease it in a vacuum.